The vampire's assistant - Shan, Darren (Shan, Darren. Saga of Darren Shan, 2004)
After traveling with Mr. Crepsley, the vampire who made him into a half-vampire, Darren returns to the freak show known as the Cirque du Freak and continues to fight his need to drink human blood.